[OA115] An international master of advanced studies in medical physics: An appraisal after 5 cycles. (August 2018) - Longo, Renata; Bertocchi, Luciano; De Denaro, Mario; Milotti, Edoardo; Padovani, Renato; Rigon, Luigi
Abstract : Purpose: There is a worldwide shortage of clinical medical physics professionals and medical physics academics. Adequate academic education and structured clinical training of medical physicists play a vital role in ensuring the safe and effective use of advanced technologies in both diagnosis and treatment. In order to address the problem of supporting high-level skills in countries without post-graduate education in Medical Physics an international Master of Advanced Studies in Medical Physics has been jointly organized by our institutions. Methods: The Master offers a study program in line with the best international practices that provides both knowledge and practical skills to graduate students. It is a two-years program: one academic year of theoretical classes followed by one year of supervised clinical training in radiotherapy or medical imaging. The clinical training is organized according to the IAEA, AFRA and IOMP guidelines. It is jointly organized by the Physics Department of the local university, and by an international scientific institution located in the same area. The university hospital actively supports the program. Most fellowships are provided by an international agency, and are supplemented by others from local or international institutions. Results: The 5th cycle of the Master was opened in 2018. Up to now 86 students have been enrolled in the Master from all the continents: 39 from Africa, 21 from Asia, 19 from Latin America, 1 from Oceania and 6 from Europe (25 women and 61 men). The cooperation between university and the international scientific institution is a recognized example of effective synergy: the university has experience in high-level education and organization of courses while the international institution has an efficient network for the international enrolment of students and a large experience in international mobility. The generous collaboration of a large number of hospitals with medical physics departments guarantees a one-year-long supervised clinical training per each student. Conclusions: The Master programme requires an extensive effort from both students and the organizing institutions, but the results are very satisfactory as the graduates are highly appreciated in the hospitals in their home countries.